Evaluating the potential of cubosomal nanoparticles for oral delivery of amphotericin B in treating fungal infection - Yang Z (Dove Medical Press, 2014)
Zhiwen Yang,1,3 Meiwan Chen,2 Muhua Yang,1 Jian Chen,1 Weijun Fang,1 Ping Xu11Department of Pharmacy, Songjiang Hospital Affiliated The First People's Hospital, Shanghai Jiao Tong University, Shanghai, 2State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, 3Shanghai Songjiang Hospital Affiliated Nanjing Medical University, Nanjing, People's Republic of ChinaAbstract: The oral administration of amphotericin B (AmB) has a major drawback of poor bioavailability. The aim of this study was to investigate the potential of glyceryl monoolein (GMO) cubosomes as lipid nanocarriers to improve the oral efficacy of AmB. Antifungal efficacy was determined in vivo in rats after oral administration, to investigate its therapeutic use. The human colon adenocarcinoma cell line (Caco-2) was used in vitro to evaluate transport across a model of the intestinal barrier. In vivo antifungal results showed that AmB, loaded in GMO cubosomes, could significantly enhance oral efficacy, compared against Fungizone®, and that during a 2 day course of dosage 10 mg/kg the drug reached effective therapeutic concentrations in renal tissue for treating fungal infections. In the Caco-2 transport studies, GMO cubosomes resulted in a significantly larger amount of AmB being transported into Caco-2 cells, via both clathrin- and caveolae-mediated endocytosis, but not macropinocytosis. These results suggest that GMO cubosomes, as lipid nanovectors, could facilitate the oral delivery of AmB.Keywords: glyceryl monoolein cubosomes, oral delivery, amphotericin B, antifungal activity, absorption mechanism